Narrative inquiry in China - Xu, Shijing; Connelly, Michael; Chi, Chenkai (Frontiers in Education, 2024)
Narrative inquiry has been widely used in different disciplines around the world. In this article, we focus on narrative inquiry in China where we start by retelling our first close contact with narrative researchers in China in 2007 when Professor Gang Ding at East China Normal University invited leading Chinese researchers to a three-day narrative inquiry workshop co-planned with us (Connelly and Xu). Second, we review narrative studies published in Chinese to demonstrate how widely narrative inquiry has been adopted in educational studies in the country in the past two decades by Chinese university researchers, graduate students, and schoolteachers. Next, our review of English literature of narrative studies related to education in China has two important components: English literature on narrative inquiry contextualized in China and narrative inquiry for Reciprocal Learning in Teacher Education and School Education Between Canada and China. Both reveal how narrative inquiry has contributed to international cross-cultural educational studies related to Chinese contexts. Finally, in the Discussion section, we provide our interpretation of some current dialogues on narrative inquiry among Chinese educational researchers; for example, the differences between Yanjiu 研究 (research) and Tanjiu 探究 (inquiry). Some heated discussions surrounding narrative inquiry in China are also highlighted, including: (1) cultural complexities in narrative inquiry, (2) theoretical frameworks in narrative inquiry, (3) re-storying and fictionalization processes in narrative inquiry, and (4) ethical considerations in narrative inquiry. To conclude, with cases selected and elaborated from the Canada-China partnership, we demonstrate how narrative inquiry has enabled us to develop “reciprocal learning” as both a conceptual framework and a methodological approach to building a multidimensional bridge for reciprocal learning in education between the West and East. This Reciprocal Learning approach reflects our global comparative studies view that the path to global cross-cultural harmony and understanding lies with collaborative action plans among people of different cultures. Writing this article on Narrative Inquiry in China enabled us to reflect on and learn from narrative inquirers and researchers in China while sharing what we have done in our own narrative inquiry.